2013
DOI: 10.1111/1755-0998.12158
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting patterns of DNA barcoding and taxonomy in the cicada genus Tettigettalna from southern Europe (Hemiptera: Cicadidae)

Abstract: DNA barcodes have great potential to assist in species identification, especially when high taxonomical expertise is required. We investigated the utility of the 5' mitochondrial cytochrome c oxidase I (COI) region to discriminate between 13 European cicada species. These included all nine species currently recognized under the genus Tettigettalna, from which seven are endemic to the southern Iberian Peninsula. These cicadas have species-specific male calling songs but are morphologically very similar. Mean CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…These values are in general agreement with the ones previously reported for Tettigettalna josei (Boulard 1982). Sequences of cytochrome c oxidase I (COI) obtained from the three specimens collected in Spain (GenBank: KF977503–KF977505) were identical to the ones reported in Nunes et al (2014) for Tettigettalna josei (GenBank: KC807267–KC807274) thus confirming species identification.…”
Section: Taxon Treatmentssupporting
confidence: 66%
See 2 more Smart Citations
“…These values are in general agreement with the ones previously reported for Tettigettalna josei (Boulard 1982). Sequences of cytochrome c oxidase I (COI) obtained from the three specimens collected in Spain (GenBank: KF977503–KF977505) were identical to the ones reported in Nunes et al (2014) for Tettigettalna josei (GenBank: KC807267–KC807274) thus confirming species identification.…”
Section: Taxon Treatmentssupporting
confidence: 66%
“…Sequences of 581 base pairs from the 5’ region of the cytochrome c oxidase I (COI) mitochondrial gene were obtained from 15 males of Tettigettalna josei . Sequences were obtained as described in Nunes et al (2014) and deposited in GenBank (accession numbers KF977491–KF977505). A minimum spanning network was constructed with the median-joining method (Bandelt et al 1999) in NETWORK 4.6.1.1 (http://www.fluxus-engineering.com).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,31,32,80]). Cicada complexes with morphologically similar but acoustically different species have repeatedly been shown to exhibit irregular mtDNA phylogenies [32,68,81,82]. …”
Section: Discussionmentioning
confidence: 99%
“…The study group Cicadas (Hemiptera: Cicadidae) are a widespread insect family found on every continent except Antarctica. The continued discovery of new species and collection of new specimens of these insects for acoustic, morphological and molecular analyses is important for understanding cicada evolution and for conservation (Gogala & Trilar, 2004;Moulds, 2005;Quartau & Simões, 2006;Gogala et al, 2008a;Marshall et al, , 2011Puissant & Sueur, 2010;Gogala et al, 2012;Popple, 2013;Nunes et al, 2014;Hertach et al, 2015). Song characters are especially powerful for species delimitation.…”
Section: Molecular Species Delimitation Methodsmentioning
confidence: 99%